Mathematical method for air electrostatic discharge circuits calculation. Issue 3 (1st September 2018) - Xinggang, Liu; Ming, Wei; Xiaofeng, Hu
Abstract : Here, a new analytical method, state matrix transform method, is proposed for calculating the descriptions of current waveforms generated by commercial electrostatic discharge (ESD) generators. This method can be used to analyse and design lumped parameter ESD circuits. A relatively simple eight elements ESD circuit model is established and used to predict the current waveform of human‐metal ESD events. To calibrate the ESD simulator, a mathematical expression of four exponentials curve for ESD current waveform is given. This careful theoretical study of ESD current waveform calculation makes an innovative contribution to ESD generator circuit simulation and design, and it provides a new mathematical description for ESD sensitivity test.